Implementation of Speech Recognition Home Control System Using Arduino - Nurul Fadzilah, Hasan; M. R. M., Rejab; Nurul Hidayah, Sapar (2015)
Electronically control of household activities has long been explored in various ways. This paper presents the development of a low cost voice home control system. This objective is accomplished by applying speech recognition into the system, with Arduino Uno as the controller. This system able to help people to use the electronics devices effectively besides provide improved convenience and comfort to user especially for elderly and disabled who live alone and help them to be more independent.